Inscrituras e Resistência Política na Obra de Patrícia Rehder Galvão (1910-1962) - Leme, Elaine Cristina Senko (2024)
In this dissertation, I propose to explore the concept of proletarian romance through the analysis of works by Patrícia Rehder Galvão (1910-1962). Pagu, the name by which she is better known, demonstrated throughout her life strong intellectual engagement and militancy against the authoritarian aspects of Brazilian politics. As part of the anthropophagic movement, inspired by Oswald de Andrade and Tarsila do Amaral, Pagu positioned herself as a defender of an authentic Brazilian culture. This stance of criticism and, as one may also reflect, resistance, was demonstrated due to her membership to the Brazilian Communist Party. Pagu's artistic manifestations come from her experiences as a political prisoner, in 1931, and from her socialist intellectual trip around the world, in 1933. Arrested in Paris in 1935, she was sent to Brazil to be tortured again by Getúlio Vargas' police, for another five years, a moment described in her autobiography. However, all of this made she stronger in the fight against reactionary political and social movements in her historical context. I understand Pagu through her writing, analyzing as an object the perspective of construction of her proletarian language. To do so, I am based on theoretical references of decolonial thought, such as: Aimé Césaire, in Discurso sobre o colonialismo (1978); Françoise Vergès, with the work Um feminismo decolonial (2020); e Pensamento feminista hoje: Perspectivas decoloniais (2020), by Heloísa Buarque de Hollanda (1940). Finally, I carry out an external and internal analysis of the following writings by the author with a view to identifying her concept of proletarian romance: the sketches (1929), her articles and drawings in the newspaper O Homem do Povo (1931), and the works Parque Industrial (1933) and Autobiografia Precoce (1940).